Politics and Monetary Policy - Ehrmann, Michael; Fratzscher, Marcel (The Review of Economics and Statistics, 2011)
How and why do politicians' preferences about monetary policy differ from the interest rates set by independent central banks? Looking at the European Central Bank (ECB), this paper shows that politicians, on average, favor significantly lower interest rates. Three factors explain the different preferences. First, politicians put relatively less weight on inflation (and more on output) in their preferred monetary policy reaction function. Second, their preferences are affected by political economy motives. Third, different preferences are also, and largely, due to different constituencies, as politicians primarily focus on national economic objectives rather than the euro area as a whole.